2021
DOI: 10.1186/s12917-021-02878-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and its association with oxidative stress in dogs with heart failure

Abstract: Background Inflammation and oxidative stress can contribute to the development and progression of heart failure. This study aimed to investigate the association between inflammatory and oxidative stress markers in dogs with congestive heart failure (CHF). Associations between the disease severity marker N-terminal pro-B-type natriuretic peptide (NT-proBNP) and markers of inflammation and oxidative stress were also determined. Results Thirty-seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
4
22
0
2
Order By: Relevance
“…An increase in neutrophil count and decrease in lymphocyte count are typical for systemic inflammation, and it is known that low-grade inflammation is present in CHF in people [ 45 , 46 ] and dogs [ 29 , 30 ]. A higher neutrophil percentage has been found in dogs with advanced-stage CHF in comparison to dogs with stable CHF and/or non-CHF dogs or healthy controls [ 29 , 30 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An increase in neutrophil count and decrease in lymphocyte count are typical for systemic inflammation, and it is known that low-grade inflammation is present in CHF in people [ 45 , 46 ] and dogs [ 29 , 30 ]. A higher neutrophil percentage has been found in dogs with advanced-stage CHF in comparison to dogs with stable CHF and/or non-CHF dogs or healthy controls [ 29 , 30 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in neutrophil count and decrease in lymphocyte count are typical for systemic inflammation, and it is known that low-grade inflammation is present in CHF in people [ 45 , 46 ] and dogs [ 29 , 30 ]. A higher neutrophil percentage has been found in dogs with advanced-stage CHF in comparison to dogs with stable CHF and/or non-CHF dogs or healthy controls [ 29 , 30 , 47 ]. Low lymphocyte counts are often found in human CVD and were shown to be a predictor of mortality in CVD patients [ 48 , 49 , 50 ], but the results of studies in dogs are contradictory, with most of them not detecting decreased lymphocyte count or percentage in canine patients with heart disease [ 29 , 30 , 38 , 39 , 47 ]; however, in one of the mentioned studies, a significantly lower lymphocyte percentage was found in CHF and non-CHF groups of canine cardiac patients compared to that in healthy dogs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations